A Qualitative Study on Factors Affecting Adherence Among Indian Haemodialysis Patients at a Tertiary Teaching Hospital of Southern India. (September 2019) - Dsouza, Brayal; Prabhu, Ravindra A; Unnikrishnan, B; Shetty, Avinash; Reshmi, Bhageerathy
Non-adherence to treatment regimen can have a detrimental effect on the heath of dialysis patients, increase mortality, morbidity and increase in healthcare service utilization and cost of hospitalization. This qualitative study explores the factors affecting adherence among the dialysis population visiting a tertiary care teaching hospital in southern India by conducting one-to-one in-depth interviews with the patients as well as key informant interview with the caregivers at the outpatient dialysis facility of a tertiary care teaching hospital. Interview transcripts were thematically analyzed using ATLAS.ti. Patient factors, health financing, cultural beliefs, caregivers' burden and health systems factors were identified. Understanding the factors affecting adherence can help the healthcare providers and the government to devise strategies to promote adherence and improved well-being among dialysis patients. Universal health coverage for dialysis, regulations to safeguard employment, creating awareness about opting for critical illness policies through private insurance companies when the disease is not pre-existing can reduce the out-of-pocket expenditure; these are some of the important areas for consideration to promote adherence.